New Horizons and Disruptions. East-German Female Directors of the DEFA-Studios and from Underground - Klauß, Cornelia (Panoptikum, 2020)
On the occasion of a publication Sie – Regisseurinnen der DEFA und ihre Filme, Berlin, Schriftenreihe der DEFA-Stiftung, 2019, all female directors who worked for the DEFA studios in the GDR were identified for the first time. More than sixty women directors worked for DEFA between 1946 and 1992. They made feature films and documentaries, worked in advertising film and in the animation studio. Particularly among the smaller formats, there is a striking number of female directors who were able to accommodate their preferred themes in the slipstream of the major productions. They problematized the official reading of equal rights and created counter-images in their figures and portraits. To be added to the canon of female filmmaking are also the independent women filmmakers, who were only allowed to realize and show their works outside the official media structures. These were female artists who discovered the film medium for themselves and made Super-8 abstract films with elements of performance on very low budgets.
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMjY4ODEvcGFuLjIwMjAuMjMuMDM